Team Resilience: Practical Implications for Military Service Members. (2nd October 2022) - Gomes, Kimberly D.; Sánchez-Cardona, Israel; Moore, Brian A.
Abstract: Team resilience is a multidimensional, multi-level construct that can be influenced by individual, team, and organizational factors. Current research indicates that team resilience enhances organizational outcomes, and potentially can contribute to efforts to enhance the well-being of individuals within the military. Despite a steadily growing literature, few studies have addressed the implications of team resilience in the military. The present monograph addresses the definition, measurement, and implications of team resilience for military personnel. Our review of the current literature indicates that theoretical models of team resilience have not been well tested in military samples. Similarly, current assessments of team resilience have not been extensively validated in military personnel. Finally, no formal training programs exist to target the development of team resilience in military personnel. Future studies would benefit from addressing these gaps in literature among different military populations (e.g., trainees, and reserve components) and if conducted appropriately could help inform the development of targeted military appropriate interventions.